2022
DOI: 10.1002/vrc2.507
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive tract infection caused by Kocuria kristinae in an entire female sugar glider (Petaurus breviceps)

Abstract: The presence of a cloaca in the reproductive tract of marsupials may predispose them to ascending infections. A 7-year-old, entire, female sugar glider presented with abdominal swelling. Whole-body radiographs and abdominal ultrasound revealed a mass in the abdomen. Initial treatment included meloxicam, buprenorphine and subcutaneous fluids. Abdominal exploratory surgery revealed a severe purulent distention of the reproductive tract with multiple adhesions to the intestines, both ureters, urinary bladder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Given the technical complexity of the surgery, the animal's small size [34], and the fact that it has not been confirmed to have a favourable impact on their health [28], to avoid unwanted gestations in this species, only males are usually neutered [34]. However, due to the presence of the cloaca, which connects the urogenital and digestive tracts, this species is relatively prone to ascending infections from the cloaca, which can cause vaginitis and metritis [35]. Sometimes, these pathologies can be resolved conservatively [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the technical complexity of the surgery, the animal's small size [34], and the fact that it has not been confirmed to have a favourable impact on their health [28], to avoid unwanted gestations in this species, only males are usually neutered [34]. However, due to the presence of the cloaca, which connects the urogenital and digestive tracts, this species is relatively prone to ascending infections from the cloaca, which can cause vaginitis and metritis [35]. Sometimes, these pathologies can be resolved conservatively [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the presence of the cloaca, which connects the urogenital and digestive tracts, this species is relatively prone to ascending infections from the cloaca, which can cause vaginitis and metritis [35]. Sometimes, these pathologies can be resolved conservatively [35]. However, when removal of the female genitalia (ovary-vagina-hysterectomy) is necessary for medical reasons, careful consideration should be given to the course of the ureters, isolating their last section from the ipsilateral lateral vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Female reproductive diseases have been poorly documented in sugar gliders [ 4 , 9 , 10 ]. Bassan et al recently reported reproductive tract infection including the uterus and central and lateral vaginal canals caused by Kocuria kristinae in an entire female sugar glider [ 1 ]. A spontaneous pathological study of the gray short-tailed opossum ( Monodelphis domestica ) revealed a few cases affected by female reproductive diseases, such as metritis, uterine cyst and endometritis [ 6 , 9 ].…”
mentioning
confidence: 99%
“…Removal of the female reproductive tract is not a common procedure for reproductive control in sugar gliders because either vasectomy or castration is preferred as surgical method and no evidence recommends elective alteration of the female sugar glider for health benefits [ 10 , 11 , 13 ]. Surgical intervention for female reproductive disease for therapeutic purposes in this species has thus been poorly reported due to the low morbidity of female reproductive disease [ 1 , 10 , 11 , 13 , 14 ]. As a result, the appropriate extent of surgical removal for female infectious reproductive disease remains open to debate.…”
mentioning
confidence: 99%